STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KEDISIPLINAN GURU DI SD NEGERI 1 BIROMARU KECAMATAN SIGI BIROMARU - Siskawati M. Taul; Jihan; Darmawansyah; Masmur M (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the Principal's Strategy in Improving Teacher Discipline at SD Negeri 1 Biromaru, Sigi Biromaru District and identifies inhibiting and supporting factors. This type of research is afield research using a qualitative approach that is descriptive. The data collection techniques used are observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and data verification. The results of this study show that: 1. The principal's strategy in improving teacher discipline at SD Negeri 1 Biromaru is carried out through several steps, including: a) Motivation, namely the principal routinely provides motivation through morning apples and teachers' four, emphasizing responsibility, example, and professionalism, so that teachers are encouraged to discipline voluntarily and are more ready to teach. b) the creation and determination of rules, namely the application of clear and consistent rules related to attendance hours, teaching hours, administration, and work ethics, which help foster discipline and order. supervision, carried out directly through classroom supervision and not directly through daily photo attendance, and equipped with weekly reflection, so that teachers are encouraged to improve the quality of work.d) giving warnings or punishments, namely through performance appraisals (SKP) and the example of the principal, such as arriving early and starting lessons on time, which encourages teachers to imitate discipline without direct reprimands. With these strategies, teacher discipline at SD Negeri 1 Biromaru can be realized in a sustainable manner. 2. Supporting and inhibiting factors in improving teacher discipline: a. support: including good cooperation between school residents, support from students' parents, and the availability of adequate facilities and infrastructure.b. Obstacles: Obstacles include teachers who are not consistent in discipline, limitations in certain facilities, and differences in students' backgrounds.